Antonín Hořejš — neúnavný propagátor nového Slovenska / Antonín Hořejš — the propagator of new Slovakia - Klára Prešnajderová (Historie - Otázky - Problémy, 2016)
During the interwar period Antonín Horejš was an important propagator of modern design in Slovakia. He was the man behind the art magazines Slovenská Grafia (Slovak Graphic Art) and Nová Bratislava (New Bratislava). The first magazine was dedicated to ‘new typography’, the other was about the social aspects of art.